Sea Surface Roughness Observed by High Resolution Radar - Atsushi Fujimura; Susanne Lehner; Alexander Soloviev; Xiaofeng Li (Remote Sensing, 2019)
Changes in the sea surface roughness are usually associated with a change in the sea surface wind field [...]